Surgically enforcing normalcy: a critical analysis of international craniofacial NGOs - Hamrick, Marley Victoria, author; DeMirjyn, Maricela, advisor; Vernon, Irene S., committee member; Kreston, Rose, committee member (Colorado State University. Libraries, 2015)
The purpose of this study is to deconstruct dehumanizing representations of children with facial differences in the Third World and catalyze a critical understanding of the work of international craniofacial non-governmental organizations, NGOs that provide free reconstructive surgery to children with facial differences around the world. This study focuses on four of those organizations – Smile Train, Operation Smile, Little Baby Face Foundation, and Operation of Hope. Considering the social, political, and economic positions of the children treated by the organizations, their messaging has powerful consequences. The research questions follow: (1) What role does ideology play in international craniofacial NGO’s representations of children with facial differences in the Third World?, and (2) To what extent and in what ways do international craniofacial NGOs address the systemic barriers faced by children with facial differences in the Third World, as portrayed by their social media materials? This study uses a multimodal critical discourse analysis (MCDA) of social media sites to explore the research questions. Findings reveal that the NGOs contribute to the problems that they aim to address. Their messaging promotes neocolonialism, ableism, heterosexism, classism, and eugenics. Ironically, these same systems of power create the lack of access to medical care, stigmatization of norm-challenging bodies, and abuse that the organizations aim to address. Considering the positive outcomes of increased survival rates and greater awareness, these findings have complex implications. Rather than arguing for the elimination of international craniofacial NGOs, this study calls for new ways to address the challenges faced by children with facial differences.